Paz e justiça: aspectos fundamentais da república mundial de Otfried Höffe - Barbosa, Ediane Soares (2014)
This work aims to show how the concepts of peace and justice are fundamental in World Republic of Otfried Höffe, guided by the defense of Human Rights which are valid worldwide. We start from a conceptualization of the two issues separately, in two early chapters, and show in a third and final chapter how they appear in a concrete way inside the tasks and the World Republic institutions. In the first chapter we present the path that the philosopher crosses to reach the concept of perpetual peace, with special attention to Kant’s work, Toward Perpetual Peace (1795), which serves as notorious inspiration to Höffe. Similarly, on the second chapter we outline Höffe’s point of view about justice, showing that he maintains dialogue with philosophers from various periods in the Philosophy History, such as Plato, Aristotle, Kant and John Rawls. With this last philosopher, Höffe keeps an important interlocution, agreeing most of times, but also criticizing and proposing new ideas. Finally, in the third chapter we try showing the integration of these two concepts in the structure of the World Republic, showing potential issues to be faced and its possible solutions. Thus, we come to the central point of our proposal: clarifying the reason why the author chooses peace as big goal of his project and identifies justice as the most appropriate to get it through.